Behavioural Responses to Unfair Institutions: Experimental Evidence on Rule Compliance, Norm Polarisation, and Trust - Simon Columbus; Lars P. Feld; Matthias Kasper; Matthew D. Rablen (Institute of Labor Economics (IZA), 2023)
This study investigates the effects of unfair enforcement of institutional rules on public good contributions, personal and social norms, and trust. In a preregistered online experiment (n = 1,038), we find that biased institutions reduce rule compliance compared to fair institutions. However, rule enforcement – fair and unfair – reduces norm polarisation compared to no enforcement. We also find that social heterogeneity lowers average trust and induces ingroup favouritism in trust. Finally, we find consistent evidence of peer effects: higher levels of peer compliance raise future compliance and spillover positively into norms and trust. Our study contributes to the literature on behavioural responses to institutional design and strengthens the case for unbiased rule enforcement.
Keywords: H41; C72; C91; C92; 330; public goods; compliance; social norms; trust; audits; biased rule enforcement; polarisation